The role of governance in explaining the relationship between public social expenditure and economic growth An econometric study on the organization of Islamic Cooperation Countries (OIC) during the period 1996- 2016 - Mahdi, Basheer Hezam; Ben Mimoun, Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
The paper aimed to study the impact of government social spending with its various components (education, health, social care) on economic growth in light of the role of governance indicators. It considered the OIC countries' experience during the 1996- 2016 period and estimated an econometric model using the "Generalized Moment Method" (GMM). The World Governance Indicators (WGI) have been used to proxy for the governance variable. The results showed that: (i) there is a negative impact of government spending on education and health in the OIC countries, and an unstable effect of spending on social transfers on economic growth; (ii) there is an interaction between government social spending on the one hand and governance on the other hand, and that the effectiveness of government social spending increases in Islamic countries with good governance indicator; and (iii) there is a positive effect of the six sub- governance indicators- except for the “voice and accountability” indicator on economic growth, and on the effectiveness of social spending on education and health on economic growth.
Keywords: Social spending; Economic growth; OIC countries